(3eZjK GdfOG Edi TQM bWQ GdfOis - (3GdTQHjfj GdeUQj GdTGaYj, TeS GdOjf (B- (3GdNWjH, eMeO Hf CMeO, J (B977 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj HYK eMeOG Udi Gddg Ydjg hSde hHYO ajbhd abjQ QMeI QHg eMeO GdNWjH GdTQHjfj gPG eG OYJ Edjg MGLI GdeJagejf dbWQ GdfOG hHd GdUOGhSejJg eZjK GdfOG Edi TQM bWQ GdfOGs
(3BNQgG (B:s
(3hEfeG de JMPa geRI Cd EPG ONd YdjgG geRI GdGSJagGe hcGf GdbjGS MPagG dFdG jdJHS GdGSJagGe HGdNHQ dGTJQGc GdgeRJjf aj GdaJMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 69s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs